Ethnographic Study of Tuberculosis Treatment Seeker Behavior on the Island of Buru, Maluku, Indonesia - Firda Yanuar Pradani; Rohmansyah Wahyu Nurindra; Usman Usman (Insights in Public Health Journal, 2020)
Background: Tuberculosis (TB) is reported as a world health problem, especially in developing countries. It is estimated that one third of the world's population has been infected by Mycobacterium tuberculosis. WHO has stated that tuberculosis has now become a global threat. Indonesia is one of the 27 countries in the world with MDR-TB cases. Methods: A qualitative study with an ethnography design was conducted to determine and reveal the meaning of treatment-seeking behavior in “Batu Balender” or TB patients in Buru Island, Maluku, Indonesia. The research data was collected through interviews with 15 informants from all risk groups that are directly related to TB. Observations were made to ensure the validity of the data. Results: This study revealed that from generation to generation, the Alifuru tribe believes that diseases are grouped into three categories: natural diseases, sick submissions, and ancestral curse. Indigenous people have believed that TB is an incurable ancestral curse disease. They know the "Kaygosa" who is believed to be the holder of natural medicinal plants to treat TB, such as leaves and bark. Conclusions: Alifuru tribal people who access health services to obtain Directly Observed Treatment Short-Course (DOTS) have experienced failure in treatment due to local customary rules that prohibit taking medicine if a tribal community has died and believes that a community health center or hospital is "house died". This study suggest that education and counseling for TB treatment should be optimized in efforts to improve the health of local tribal communities.